Analysis of Energy Use Intensity (EUI) Factors in Government Office Buildings in Tropical Climate: A Case Study in the Ministerial Office Building and the Directorate General of Water Resources Building of The Ministry of Public Works - Kusumastuti, Diana; Setyowati, Erni; Sari, Suzanna; Dwiyanto, Agung (Diponegoro University, 2025)
Energy Use Intensity (EUI) is a key indicator for evaluating the energy efficiency of buildings. This study aims to analyze the EUI factors in two government office buildings: the Ministerial Office (MO) building and the Directorate General of Water Resources (DGWR) building of The Ministry of Public Works. Both are located in close proximity and share similar physical characteristics under tropical climate. The EUI is analyzed using the walkthrough audit method as a practical approach for assessing energy performance. The results show that the DGWR Building exhibits higher energy consumption, primarily due to the dominance of cooling loads accounting for 54.13% of the total EUI, compared to 46.54% at the MO building. There are three main factors contributing to the EUI variation include: (i) heating, ventilation, and air conditioning (HVAC) system – the water-cooled chiller used in the MO building shows higher efficiency compared to the air-cooled chiller system installed in the DGWR building; (ii) Overall Thermal Transfer Value (OTTV) – although both buildings utilize similar envelope materials, the OTTV value in DGWR building is significantly higher due to its larger window-to-wall ratio (WWR), which increases heat gain through the facade; and (iii) Lighting – while there is no significant difference in total installed lighting power, the higher lighting power density (LPD) in DGWR building contributes to a greater lighting energy load per unit area. Additionally, the implementation of smart lighting systems in MO building contributes to better energy efficiency performance.